End-Stage Renal Disease in Familial Amyloidosis ATTR Val30Met: A - Lobato, L. (2010)
Transplant Proc. 2003 May;35(3):1116-20. End-stage renal disease in familial amyloidosis ATTR Val30Met: a definitive indication to combined liver-kidney transplantation. Lobato L, Ventura A, Beirão I, Miranda HP, Seca R, Henriques AC, Teixeira M, Sarmento AM, Pereira MC. Department of Nephrology, and Liver Transplantation Program, Hospital Geral de Santo António, Largo Professor Abel Salazar, 4050, Porto, Portugal. llobato@nctcabo.pt PMID: 12947881 [PubMed - indexed for MEDLINE]